Weird Yet Strange : Notes from an Austin Music Artist - Garrett, Danny, 1945- (Book collections on Project MUSE., 2015)
"This book is a collection of the music art I did from 1971 to 2015 in Austin, Texas. Most of these images are posters. Austin music is vast. So too is the art that pictured it, and this collection is just my little corner of that art. It does, however, deal with some significant arenas of that music: Armadillo World Headquarters, Antone's, Progressive Country, outdoor events, and work that I did for Willie Nelson and Stevie Ray Vaughan. In that regard, I would like to offer this work as a partial visual chronicle of what took place in Austin music in the formative decades of the 1970s and 1980s."--Page xi.